Optimizing Supply Chain Transportation with Centralized Logistics in Industry Y Wholesale: Case: Company X - Kettunen, Kasperi (My University, 2019)
Transportation of goods has consistently increased and become an integral part of the global growth of supply chains. Logistic management with transportation as a core part continues to provide a structure for distributing products on an international scale. Logistic processes are a significant part of wholesale management thus optimizing these processes can provide substantial competitive advantages. This research was conducted as a contract for a Finnish wholesaler operating in industry Y. The purpose of this study was to investigate the causes of supply chain fragmentation and how to mitigate these effects. The objective was to investigate how a centralized logistic system can provide benefits to the inbound process of the case company. The central concepts are sustainable logistics, supply chain visibility, lean distribution, discrete event simulation as well as supply chain modelling. The empirical research employs a mixed research method. Quantitative data is used from the arrived inbound deliveries and qualitative data is gathered from a questionnaire conducted in the case company about the inbound processes. The collected data is used to form an understanding of the current inbound processes and to construct a centralized pipeline system. Comparing these two systems identifies any inefficiency as well as highlights the benefits that the pipeline system can provide. The current logistic system operates with insufficient visibility to incoming shipments for the case company. The information flow is fragmented between processes and supply chain members. The research results indicated that a centralized pipeline system can provide improvements to the information flow, higher used freight capacity and reduced CO2 emissions of the logistic processes. However, implementing a centralized pipeline system would require further research, as the logistic processes are complex and require in-depth analysis with an expanded scope.
Keywords: Supply chain management; Industry Y logistics; Lean distribution; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|